1992
DOI: 10.1037/0735-7044.106.5.739
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar stimulation as an unconditioned stimulus in classical conditioning.

Abstract: Rabbits were implanted with chronic stimulating electrodes in white matter underlying lobule HVI of the cerebellar cortex. Stimulation elicited movements of the face or neck and, when paired with a tone conditioned stimulus (CS), produced learning comparable to that seen with peripheral unconditioned stimuli (USs). CS-alone trials produced extinction. Reinstatement of paired trials produced reacquisition with savings. Additional groups received either explicitly or randomly unpaired CS-US trials before paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 45 publications
(69 reference statements)
2
19
0
Order By: Relevance
“…Previous recording (e.g., Berthier & Moore, 1986;McCormick & Thompson, 1984;Schreurs, Gusev, Tomsic, Alkon, & Shi, 1998), stimulation (e.g., Katz, Tracy, & Steinmetz, 2001;Swain, Shinkman, Nordholm, & Thompson, 1992), lesion (e.g., Lavond & Steinmetz, 1989;Yeo, Hardiman, & Glickstein, 1985), and inactivation studies (Attwell, Rahman, Ivarsson, & Yeo, 1999;Attwell, Rahman, & Yeo, 2001) indicated that lobule HVI plays a critical role in eyeblink conditioning in rabbits. The stereotaxic coordinates for HVI were taken from lambda (AP ¼ À2.3 mm; ML ¼ þ2.3 mm; and DV ¼ À1.5-À3.0 mm).…”
Section: Surgerymentioning
confidence: 99%
“…Previous recording (e.g., Berthier & Moore, 1986;McCormick & Thompson, 1984;Schreurs, Gusev, Tomsic, Alkon, & Shi, 1998), stimulation (e.g., Katz, Tracy, & Steinmetz, 2001;Swain, Shinkman, Nordholm, & Thompson, 1992), lesion (e.g., Lavond & Steinmetz, 1989;Yeo, Hardiman, & Glickstein, 1985), and inactivation studies (Attwell, Rahman, Ivarsson, & Yeo, 1999;Attwell, Rahman, & Yeo, 2001) indicated that lobule HVI plays a critical role in eyeblink conditioning in rabbits. The stereotaxic coordinates for HVI were taken from lambda (AP ¼ À2.3 mm; ML ¼ þ2.3 mm; and DV ¼ À1.5-À3.0 mm).…”
Section: Surgerymentioning
confidence: 99%
“…These observations have been replicated and extended in recent years . Swain et al (1992) used a tone CS and showed that stimulation of cerebellar white matter in lobule HVI (rabbit) did indeed elicit movements: eyeblink, NM extension, and movements of the head and upper lip. These movements all conditioned, extinguished, and reconditioned to a tone CS in a manner identical to CRs established with aversive peripheral USs.…”
Section: The Us Pathwaymentioning
confidence: 99%
“…Examination of CS-only probe trials during training indicated that the animals displayed similar conditioned responses to both CSs suggesting that the animals had formed similar associations between both CSs and the UCS. In a different study, Swain et al (1992) employed electrical stimulation of cerebellar white matter (and presumably climbing fibers) as the UCS. Early in training, this stimulation elicited only single responses.…”
Section: Role Of the Inferior Olivementioning
confidence: 99%
“…To explore this question, Swain et al (1992) conducted a parametric study in which they stimulated the white matter immediately underlying rabbit lobule HVI. They chose this site because it was distant from brainstem and spinal reflex pathways.…”
Section: Role Of the Inferior Olivementioning
confidence: 99%